Management Strategies for Sexuality Complaints after Gynecologic Cancer: A Systematic Review - Luciane Machado Pizetta; Augusto da Cunha Reis; Mirian Picinini Méxas; Vanessa de Almeida Guimarães; Carmen Lucia de Paula (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To explore the main sexuality complaints of gynecologic cancer survivors after treatment and to identify the care strategies provided. Data Source Searches were conducted in six electronic databases: Scopus, Web of Science, LILACS, MEDLINE, PsychINFO, and EMBASE. Study Selection Articles published between 2010 and 2020 were selected and the following descriptors were used in the English language: female genital neoplasms and gynaecological cancer. The methodological quality of the studies used the Mixed Methods Appraisal Tool (MMAT). Data Collection The primary data extracted were: names of the authors, year of publication, country of origin, objective and type of study, data collection instrument, sample size and age range, types of cancer, and symptoms affected with the strategies adopted. Data Summary A total of 34 out of 2,536 screened articles were included. The main strategies found for patient care were patient-clinician communication, practices for sexuality care, individualized care plan, multiprofessional team support, and development of rehabilitation programs. For sexuality care, the most common practices are pelvic physiotherapy sessions and the use of vaginal gels and moisturizers. Conclusion The main complaints identified in the scientific literature were low libido and lack of interest in sexual activity, vaginal dryness, pain during sexual intercourse, and stenosis. Different care strategies may be adopted, such as follow-up with a multidisciplinary health team and sexual health rehabilitation programs, which could minimize these symptoms and ensure the quality of life of patients.